Instability of the interface of two viscous fluids moving in a channel. Part II a. Nonlinear problem - Tran, Tran Van (Vietnam Journal of Mechanics, 1989)
In this paper, the method of multiple scaling is used for obtaining the am-altitude evolution equations from the weakly nonlinear problem of hydrodynamic stability of concurrent flow of two viscous fluids in a channel It. is shown that in the case of stability the, interface may evolve to some finite amplitude with periodic steady state.